Investigating the idiosyncratic learning paths of elite canadian coaches - Werthner, P.; Trudel, P. (International Journal of Sports Science and Coaching, 2009)
Researchers have investigated how coaches, from the recreational to the elite level of coaching, learn to coach. Many different learning situations have been identified in the research, yet the question remains: How is it that one coach's learning path emphasizes certain learning situations as key, and yet another coach's learning path emphasizes quite different situations? Fifteen Canadian Olympic coaches were interviewed to better understand the coaches' idiosyncratic learning-path phenomena. The findings provide an example of: (a) how coaches within a specific and similar context, in this case Olympic level sport, can differ dramatically regarding the importance that common learning situations have played in their development, and (b) how previous learning and experiences influence what coaches choose to pay attention to and therefore choose to learn. The coaches' idiosyncratic learning paths are also discussed in terms of coach development.